Downstream trends of in vitro bioassay responses in a wastewater effluent-dominated river. (December 2018) - Daniels, Kevin D.; VanDervort, Darcy; Wu, Shimin; Leusch, Frederic D.L.; van de Merwe, Jason P.; Jia, Ai; Snyder, Shane A.
Abstract: Surface waters are becoming increasingly influenced by wastewater effluents due to drought conditions, growing populations, and urbanization. These effluents contain mixtures of trace organic compounds (TOrCs), including bioactive constituents, which are not fully attenuated by conventional wastewater treatment systems. This study investigated the occurrence of glucocorticoid receptor (GR), aryl hydrocarbon receptor (AhR), and estrogen receptor (ER) activity, as well as the overall toxicity to bacteria (BLT-Screen), in the effluent of two wastewater reclamation facilities (WRF) and downstream of the Lower Santa Cruz River, Pima County, Arizona USA, which is dominated by the WRF effluents. The GR, AhR, and ER activities and toxicity to bacteria were determined by in vitro bioassays during four seasons. Bioassay results showed the highest activities at the wastewater outfalls, with activities decreasing downstream of the river. Biological equivalent concentrations ranged from 9 to 170 ng/L dexamethasone-equivalents (DexEQ), 0.1–0.8 ng/L 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-equivalents (TCDDEQ), and <0.005–0.8 ng/L estradiol equivalents (EEQ) for GR-, AhR- and ER-mediated activity, respectively. This level of biological activity at times exceeded the relevant effects-based trigger value for environmental effects, indicating a potential risk to the receiving environment. Toxicity to bacteria was low at all sites, well below the trigger value of 1.0 TUIC20, which represents an undiluted water sample causing 20% toxicity in the assay. The potential inducing glucocorticoid agonists were further analysed by liquid chromatography coupled to tandem mass spectrometry. Analytical results reveal triamcinolone acetonide as the most abundant glucocorticoid with concentrations up to 38 ng/L. Similar results for DexEQ concentrations calculated from both chemical and bioassay data indicate a successful mass balance for glucocorticoids. This mass balance illustrated lower DexEQ during summer months, which could be due to an increased attenuation from photodegradation. Highlights: In vitro bioactivity in an effluent-dominated river measured quarterly for one year. Bioactivity was attenuated with distance from effluent discharge without dilution. Triamicinolone acetonide most abundant glucocorticoid pharmaceutical detected. Biological activity exceeded effects-based trigger values for environmental effects.